Trends in teenage talk : corpus compilation, analysis, and findings - Stenström, Anna-Brita, 1932- (Studies in corpus linguistics, 2002)
Teenage talk is fascinating, though so far teenage language has not been given the attention in linguistic research that it merits. The dearth of investigations into teenage language is due in part to under representation in language corpora. With the Bergen Corpus of London Teenage Language (COLT) a large corpus of teenage language has become available for research. The first part of Trends in Teenage Talk gives a description how the COLT corpus was collected and processed; the speakers are presented with special emphasis on the recruits and their various backgrounds; ending with a description what the COLT teenagers talk about and how they do it. The second part of the book is devoted to the most prominent features of the teenagers talk: slanguage ; how reported speech is manifested; a survey of non-standard grammatical features; the use of intensifiers; tags; and interactional behaviour in terms of conflict talk.